Pareto optimality in the extraction of fossil fuels and the greenhouse effect: a note - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2007)
This note generalizes the Solow-Stiglitz efficiency condition for natural resources to the problem of fossil fuel extraction with a greenhouse effect. The generalized optimality condition suggests that the greenhouse effect implies overextraction in the sense of leaving future generations a wrongly composed wealth portfolio with too few natural resources relative to man-made capital. This judgment is independent of society's ethical preferences concerning the well-being of future generations.
Keywords: O13; Q32; Q54; 330; Klimaveränderung; Treibhausgas; Fossiler Energieträger; Rohstoffressourcen; Generationenbeziehungen; Pareto-Optimum; Theorie